A tale of two cities: exploring the retail impact of flavoured tobacco restrictions in the twin cities of Minneapolis and Saint Paul, Minnesota. Issue 2 (6th June 2018) - Brock, Betsy; Carlson, Samantha C; Leizinger, Alicia; D'Silva, Joanne; Matter, Christine M; Schillo, Barbara A
Abstract : Background: Flavoured tobacco is increasingly popular with youth. The twin cities of Minneapolis and Saint Paul, Minnesota restricted the sale of flavoured tobacco to adult-only tobacco shops in an effort to reduce youth access and exposure to these products. This observational study explores the impact of these policies on the retail environment. Methods: Between November 2015 and April 2017, observational assessments were conducted at convenience and grocery stores preimplementation and postimplementation of flavoured tobacco restrictions in Minneapolis (n=41), Saint Paul (n=37) and the comparison city of Brooklyn Park, Minnesota (n=14). Results: After policy implementation, significantly fewer of the convenience and grocery stores sold flavoured tobacco in Minneapolis (85.4% vs 39.0%, p<0.001, n=41) and Saint Paul (97.3% vs 8.1%, p<0.001, n=37). The average proportion of tobacco inventory that was unflavoured increased significantly in Minneapolis (42.9%±2.7% vs 56.7%±3.1%, p=0.002) and Saint Paul (40.8%±2.5% vs 70.3%±1.9%, p<0.001). Flavoured tobacco was available at significantly fewer convenience and grocery stores in Minneapolis (39.0%, p<0.001) and Saint Paul (8.1%, p<0.001) than in the comparison city of Brooklyn Park (100%, n=14). Most retailers complied with these policies by removing flavoured tobacco from their shelves. Conclusions: Policies that restrict the sale of flavoured tobacco to adult-only tobacco shops are associated with decreased availability of flavoured tobacco in convenience and grocery stores and increased proportion of tobacco inventory that is unflavoured.